A general and robust strategy for in-situ templated synthesis of patterned inorganic nanoparticle assemblies. (December 2021) - Liu, Peijiang; Peng, Jianping; Chen, Yutong; Liu, Mei; Tang, Wen; Guo, Zi-Hao; Yue, Kan
Highlights: Achieving in situ synthesis of patterned inorganic assemblies with tunable sizes. Block copolymer brushes templated preparation of 2D assemblies of nanomaterials. Vertical growth strictly limited by the template for efficient thickness control. Generally applicable for various metal and metal oxide compositions. Abstract: Precisely controlling the spatial organization of inorganic nanoparticles is essential for many applications, such as sensing, catalytic, and optical/electronic systems. Here, we describe a general and robust strategy to fabricate arbitrary quasi-two-dimensional (quasi-2D) nanoparticle assembly structures with tunable size and thickness on a substrate by using block copolymer brushes as the templates. To achieve this, patterned amphiphilic block copolymer brushes were first grown via light-mediated surface-initiated atom transfer radical polymerization. The hydrophilic polymer blocks could interact and enrich the inorganic precursors, and thus accelerate the in-situ growth of nanoparticles within the patterned hydrophilic polymer domains. In our method, the block copolymer template could strictly limit the vertical growth of quasi-2D nanoparticle assemblies to achieve thickness control in the nanometer scale. By changing the design of the photomask and experimental conditions for the light-mediated polymerization, quasi-2D inorganic nanoparticle assemblies with controllable shape and dimension can be feasibly obtained. Moreover, this method is also generally applicable to prepare various patterned inorganic nanoparticle assemblies with different compositions. Graphical abstract: Using patterned amphiphilic polymer brush as the nano-reactor template, we develop a general and robust in-situ synthesis strategy to assemble inorganic nanoparticles of diverse compositions into arbitrarily custom-shaped quasi-two-dimensional patterns with precisely-defined dimension and thickness on a substrate. Image, graphical abstract